Legal eagles - Medjuck, Joe; Gross, Michael C; Reitman, Ivan (Universal City, California : Universal Studio, 2003)
A hard-nosed assistant district attorney and an imaginative defense attorney combine their talents to defend a spacey'performance artist' which is accused of heft and murder.
Videodisc release of the 1986 motion picture
Screenplay, Jim Cash & Jack Epps ; story, Ivan Rreitman, Jim Cash & Jack Epps ; production design, John De Cuir ; director of photography, Laszlo Kovacs ; music, Elmer Bernstein
Cast : Robert Redford, Debra Winger, Daryl Hannah, Brian Dennehy, Terence Stamp, Steven Hill
Keywords: Trials (Murder) -- United States -- Drama